Ecological territory and ecocity as result of smart, sustainable, integrated planning policies - Stefano Aragona (European Regional Science Association (ERSA), 2016)
Objectives The purpose of the paper is to consider the natural and cultural resources as key elements in the planning and design of the territory and the city. That is to think the local conditions as guidelines in the transformations both of the space and the social environment. So overturning the logic that in most cases has guided the formation of the modern city: i.e. to build everywhere without caring the sustainability of the areas and thinking the land as an infinite resource. The chances and opportunities possible thank to smart city must be used by a 'cultured technology' (Del Nord, 1991) to build 'local Communities inclusive and sustainable, either materially and socially' (Smart City, 2010), that is "ecological". Methods A multidisciplinary vision, thus multicriteria, is the base of the proposed methodology. It requires an integrated approach of material and immaterial elements. With the overall vision that characterizes the Leipzig Charter (2007) where it are required "planning strategies that connect rural and not rural areas, small, medium, big towns, metropolitan areas". And the focus that Smart City gives to the flows of things and energy, with the goals of Horizon 2020. The starting point consists in considering the city as common good characterized by a number of physical and social local resources. Remembering that the mission of the modern town planners, from the Athena Chart 1931, is the wellbeing of the inhabitants. Renewable resources and interactive communications may help to better the design. But all that must be done having as goal construct local communities and not only to reinforce individual power. Flows of energy and flows of communications characterize the contemporaneous city: the immaterial city (Aragona, 1993, 2000). The town, its shape, its economical structure and the functional one, are changing. For the most the town planners accept these changes without trying to address them. In the countries where the city as common good is less felt these changes for bettering wellbeing and social sustainability are not caught or left to the 'free market' alone. while Ecolonia ( 1989-1993) or Sustainable Copenhagen (2009) are examples of what can be done. All this leads to redevelop the territory and the cits using indicators of life quality, going beyond GDP as the 134 of the Fair and Equitable Wellbeing and (BES) proposed by ISTAT alongside those suggested by the Charter of Quality by AUDIs since 2007. Conclusions The current crisis, can be a turning point - the meanings of the originary Greek word ?????? - of the model based on the industrial paradigm (Kuhn, 1962) whose limits were declared in "The Limits of Growth" (1972). This paper suggests to replace the industrial model of 'making the city' with the ecological approach that starts from the local conditions such as indications of plan/project/construction for the transformation of the anthropocosmo. That is to relate the ?????, discourse, analyses, with the ?????, the environment (www.ekistics.org): finally the purpose of Smart City.
Keywords: 330; Ecologica approach; Integrated town planning; Crisis as opportunity